Numerical investigation of coal particle stream ignition in oxy-atmosphere. (1st April 2019) - Farazi, Sima; Hinrichs, Jörn; Davidovic, Marco; Falkenstein, Tobias; Bode, Mathis; Kang, Seongwon; Attili, Antonio; Pitsch, Heinz
Highlights: Modeling of particle stream ignition applying the CPD method and detailed chemistry. Analysis of the ignition delay time for different number density of the particle stream. Detailed analysis of the slip velocity effect on temperature and ignition delay time. Abstract: The ignition of a stream of coal particles under oxy-fuel atmosphere is studied numerically in a laminar flow. Devolatilization of coal particles is modeled with the chemical percolation devolatilization (CPD) method coupled with a detailed chemistry model for homogeneous reactions. The particle and gas phase interactions are modeled with a fully coupled Euler-Lagrange code. A parametric study is performed to investigate the influence of particle number density, gas temperature, and velocity on ignition. We found that increasing particle number density delays the onset of ignition. Delayed ignition in denser streams is due to the lower gas temperature, which is caused by the higher energy required for particle heating. In addition, increasing particle number density leads to a more continuous and narrower flame front. Particle heating and ignition induce velocity variations in the gas phase through the coupling with particles. In the denser stream, velocity variations become significant and compromise the validity of a constant velocity assumption that is usually made in computing ignition delay time from the observed ignition location. It is also found that high particle slip velocities lead to a locally low volatile concentration and low temperature, and consequently increase ignition delay time.